A systematic validation of the Empathic Handover approach guided by five factors that foster empathy in design. Issue 4 (2nd October 2019) - Smeenk, Wina; Sturm, Janienke; Terken, Jaques; Eggen, Berry
Abstract: This study aims at validating the transferability of the Empathic Handover approach, which we originally developed for the co-design process of a dementia simulator. We argue that empathy in design is operationalised using five factors: emotional interest, sensitivity, self-awareness, personal experience, and mixed perspectives. This heuristic proved useful in systematically comparing the empathic capacity of design students using the Empathic Handover and traditional user research approaches. Our comparative study indicates that the Empathic Handover approach enables designers to develop empathy with vulnerable users they did not meet in person (both people with dementia and people who mourn). Additionally, the study enables us to develop an elaborate notion of the working mechanisms of empathy in design as well as practical improvements to the Empathic Handover approach.